Adsorption of Ciprofloxacyn by Plate-Like Bi4Ti3O12 - Manunggal, Pinky Lintang Satriani; Prasetyo, Anton (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2025)
Antibiotic compound waste has attracted significant attention because of its harmful effects on aquatic environments. One of the methods reported as a potential approach for antibiotic wastewater treatment is adsorption. Bi4Ti3O12 is a triple-layer Aurivillius compound reported to exhibit adsorption properties, although research remains limited. Therefore, we synthesized plate-like Bi4Ti3O12 using the molten salt method. The adsorption test results showed that Bi4Ti3O12 reduced ciprofloxacin concentration by 51% within 120 minutes. It shows that Bi4Ti3O12 has the excellent capability to adsorb the antibiotic compound ciprofloxacin. Keywords: Ciprofloxacin, Adsorption, Bi4Ti3O12